Ikhwan al-Muslimin and Political Movement : (A Study of Hasan al-Banna’s Thought) - Tahir, Gustia (Al-Hikmah, 2023)
The Muslim Brotherhood is a movement founded by Hasan al-Banna in 1928. The aim of this movement was originally to spread Islamic values. However, in its development, the teachings of the Muslim Brotherhood spread beyond Egypt and grew into a political movement with the aim of ending British colonial control and destroying all Western influence. The organization's goal is to establish a state governed by sharia law with the slogan "Islam is the solution". This research aims to explore al-Hasan al-Banna's thoughts through the Muslim Brotherhood movement which was able to spread out to various countries with the political ideology it carries. The data is extracted from various writings with historical and political approaches. The results of this research show that Hasan al-Banna had progressive ideas to advance Islam through political channels. For him, through this way, aspects of the life of Muslims, such as economic, social, educational and cultural, can be improved.